A DESCRIPTIVE STUDY OF ENGLISH WORDS INTERFERENCE USED IN “JAWA POS” NEWSPAPER PUBLISHED ON MARCH 2018 - Sinta Wahyu Lestari; Wahyu Kyestiati Sumarno (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2018)
Newspapers are a medium of written informations which are published every day. There is a newspaper that has been famous especially in Java that is “Jawa Pos” newspaper. “Jawa Pos” newspaper is written in Indonesian, but in presenting the information or news, sometimes the author add or insert some English words to emphasize the reader about the information to be conveyed. This style is called interference in Sociolinguistics. Considering that statement, this study wants to analyze the types of interference found in “Jawa Pos” and analyze the reasons of those interference usage. This study uses descriptive qualitative method in conducting the research. The data sources for this research are 4 edition of “Jawa Pos” newspaper, which were from 8th until 11th March 2018. The first findings of this research was 147 interferences were occured in the data sources. The result then were divided into four categories. They were 97 interferences of noun, 34 interferences of verb, 15 interferences of adjective and 1 interference of adverb. The second findings, there were 101 interference occured with prestige feeling motive as the reason, and 46 interferences were caused by need feeling motive. Based on this research, for the newspaper author the researcher wants to suggest that by using another language such as English we can increase our vocabulary in English. Futhermore, for the other researcher interference are still open to be studied because this study only focus on analysis of interference in the form of word. Meanwhile, a study of interference which focus on phrase or clause still interested to be studied.